A Study of Awareness of Nutrition & Anaemia Among College Going Students of Mahila College of Bhavnagar - Patel, Harshad; Solanki, Harsha; Gosalia, Vibha; Vora, Falguni; Singh, M. P. (National Journal of Community Medicine, 2013)
Background: The lives of young population are characterized by limited education, lack of knowledge pertaining to health aspects & also limited influence on decisions affecting their lives. Thus, awareness is one major factor for development of this group of population. Aim & Objectives: 1) To study awareness regarding nutrition & anaemia amongst young college going students. 2) To assess the impact of health awareness programme on knowledge of nutrition & anaemia. Materials & Method: Present cross-sectional study was conducted among representative group of 68 young girls from Mrs. N.C.Gandhi & Mrs. B.V.Gandhi Mahila Arts & Commerce College, Bhavnagar city. Pre test was carried out before beginning the programme followed by post test to assess the impact of health awareness programme. Health Awareness programme was carried out by Department of PSM, Government Medical College of Bhavnagar on 24th January 2012 on Nutrition & anaemia. Results: The knowledge of girls regarding health aspects improved significantly after intervention. There was a considerable increase in the awareness levels of girls with regard to knowledge of nutrition & anaemia. Conclusion: The informative & educable intervention definitely has a positive effect on awareness levels which would eventually encourage expansion of knowledge & positive health habits.